Gestão do cuidado de enfermagem em pediatria: desenvolvimento e avaliação de protótipo de aplicativo baseado na filosofia Lean Healthcare - Cicogna, Elizelaine de Chico (Universidade Federal de São Carlos, 2023)
Understood as a great encouragement to the quality of life of the population, the evaluation of the quality of the health service has been highlighted among the themes of global importance. Essential for the success of health management, knowledge of the service supports the decision-making process, and this can be obtained through indicators. Continuous measurement leads to the development of indicators that allow evaluating the performance of health services. From the observation of the processes based on activities that reflect the quality of the service, the manager optimizes his resources and increases the efficiency and quality of the service. Having Lean Healthcare and its principles and values as a theoretical framework, the objective of this thesis was to develop and evaluate an application model based on Lean Healthcare principles for the management of nursing care in a pediatric hospital unit. Developed from the Power Apps® platform for mobile devices and considering the particularities of the pediatric unit under study, the prototype application called Cronoanálise & Indicadores da Assistência (C&IA) allowed professionals to online record the activities and times of nursing care. From a Power BI® panel, the assistance information will allow monitoring of all occurrences in the unit, thus allowing the manager to have privileges to intervene just-in-time. Data collection and evaluation in the pediatric unit were carried out between the period of Nov/23/2022 thru Dec/05/2022 with 18 nursing professionals. In its results made available in Power BI®, information was transmitted about the care dynamics, indicators, processes, and workload considering the context, the team, and the assisted client. After using the application in the pediatric unit, between Dec/05/2022 and Dec/30/2022, the C&IA went through other expectations planned in the usability instruments (System Usability Scale - SUS), quality (Software Quality) and recommendation (Net Promoter System – NPS). All estimates made by 11 managers of pediatric health services and nursing professionals at the pediatric unit ended with approval rates among the evaluators, with the C&IA being recommended by the managers. The use of information technology has shown that it can contribute to the advancement of knowledge and an automated system can direct nursing practice towards actions directly to the patient. In this way, investing and promoting a team after knowing its skills and needs, considering the context and the public to which this assistance is provided, is to guarantee efficiency to the main actions of the team and, consequently, seek, in continuous improvement, guarantees for the quality of care of nursing.
Management of nursing care in pediatrics: development and evaluation of an application prototype based on the Lean Healthcare philosophy
Keywords: Gestão em saúde; Carga de trabalho; Serviços de saúde; Tecnologia em saúde; Indicadores de saúde; Informática em saúde; Aplicativos em dispositivos móveis; Enfermagem pediátrica; Segurança do paciente; Health management; Workload; Health services; Health technology; Health indicators; Health informatics; Applications on mobile devices; Lean healthcare; Pediatric nursing; Patient safety; Lean healhcare; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PEDIATRICA